When Is It Acceptable to Lie? Interpersonal and Intergroup Perspectives on Deception. Issue 2 (14th March 2016) - Dunbar, Norah E.; Gangi, Katlyn; Coveleski, Samantha; Adams, Aubrie; Bernhold, Quinten; Giles, Howard
Abstract : While deception is generally viewed as an undesirable and unethical action, people evaluate some lies as more detrimental than others. This study examined factors influencing deception assessments, including the seriousness of the lie and whom it benefits. The effect of an intergroup versus an interpersonal context for the lie was examined. Utilizing 24 vignettes varying in terms of these conditions, 259 participants evaluated a lie's appropriateness, deceptiveness, and complexity. Altruistic and white lies were viewed as less deceptive and more acceptable than self-serving and more consequential lies. Lies evaluated as least acceptable were interpersonal, serious, and self-serving compared to altruistic lies and those embedded in an intergroup context. Intergroup and interpersonal deceptions are recognized as distinct forms of lying and are evaluated differently.